The impacts of COVID-19 on global trade: Nexus of wheat and crude oil - Emam, Abda; Osman, Amira; Elmasaad, Egbal; Hadid, Maha; Elrasheed, Mutasim (Edelweiss Applied Science and Technology, 2024)
This study targeted to disclose the impact of COVID-19 on the world global trade, namely, the relationship between world crude oil prices and world wheat prices. It depended on data which was collected from different resources and covered the period extend from Jan. 2016 to Aug. 2023. The data was divided in to three periods: before COVID-19 (from Jan. 2016 to Nov. 2019), after outbreak of COVID-19 (from Dec. 2019 to Dec. 2020) and after recovering from epidemic outbreak (Jan. 2021 to Aug. 2023). Engel-Granger Two Steps Procedure and ARDL bounds methods of analysis were used to analysis data. The results for the period before and recovering from outbreaks of covid-19 revealed long run co-integration among crude oil and wheat prices series. While the result for the period after outbreaks of COVID-19 didn't discover any the long run relationship between world crude oil prices and world wheat prices. This result may be due to consequences and lockdown of COVID-19. Consequently, these results affect global food security situation.